2017
DOI: 10.1155/2017/9601735
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration of Thyroid Nodules Using the Bethesda System for Reporting Thyroid Cytopathology: An Institutional Experience in a Rural Setting

Abstract: Background. Fine needle aspiration (FNA) remains the first-line diagnostic in management of thyroid nodules and reduces unnecessary surgeries. However, it is still challenging since cytological results are not always straightforward. This study aimed to examine the results of thyroid FNA using the Bethesda system for reporting thyroid cytopathology (TBSRTC) to establish the level of accuracy of FNA procedures in a rural practice setting. Method. A retrospective chart review was conducted on existing thyroid FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
3
21
0
1
Order By: Relevance
“…In the present study, female patients outnumbered the male patients, similar to other studies. [3][4][5][6][7] The mean age of the patients at presentation was 41.2 years in our study, similar to study by Yang et al 4 Most of our patients belonged to the 31-40 years age bracket, similar to the study by Arul et al 5 , who also had majority of their cases clustered in the third decade. We compared the findings of our study with that of various other studies as shown in TABLE 5.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, female patients outnumbered the male patients, similar to other studies. [3][4][5][6][7] The mean age of the patients at presentation was 41.2 years in our study, similar to study by Yang et al 4 Most of our patients belonged to the 31-40 years age bracket, similar to the study by Arul et al 5 , who also had majority of their cases clustered in the third decade. We compared the findings of our study with that of various other studies as shown in TABLE 5.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, ND/UNS cases were 4.9 %, similar to the study by Arul et al 5 The smears which were predominantly haemorrhagic, or contained cyst fluid only were reported under this category. The percentage of cases in the benign category was 83.68% in our study, comparable to other studies by Reddy et al, 3 Mehra et al, 8 Mondal et al, 9 and Guo et al 6 Studies by Yang et al, 4 Arul et al, 5 Jo et al 10 had comparatively lesser benign cases. The high incidence of benign cases in our study can be attributed to the fact that our hospital caters to the general population in the area where it is located.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, thyroid nodules with relatively TI-RADS high scores received FNA, so total ROM of Bethesda system III/IV was 54.2%, which was significantly higher than those from Western practice, 29,[32][33][34] demonstrating that TI-RADS reduces the number of unnecessary thyroid nodule FNAs. 35 Second, as we know differentiated thyroid carcinoma (DTC) accounts for more than 90% of all thyroid cancers and DTC is an indolent carcinoma, our practice of triaging patients with Bethesda system III/IV nodules is as follows:…”
Section: Discussionmentioning
confidence: 52%
“…In our study, thyroid nodules with relatively TI‐RADS high scores received FNA, so total ROM of Bethesda system III/IV was 54.2%, which was significantly higher than those from Western practice, demonstrating that TI‐RADS reduces the number of unnecessary thyroid nodule FNAs . Second, as we know differentiated thyroid carcinoma (DTC) accounts for more than 90% of all thyroid cancers and DTC is an indolent carcinoma, our practice of triaging patients with Bethesda system III/IV nodules is as follows: ≥TI‐RADS 4c with Bethesda system III/IV nodules were referred to surgery; ≤TI‐RADS 4a with Bethesda system III/IV nodules were referred for routine observation, with the exception of benign thyroid nodules, which were referred to surgery; for TI‐RADS 4b with Bethesda system III/IV nodules needing further discussion with the patients, possible advice included repeat FNA diagnostic surgery, routine observation, use of other imaging modalities, and so on based on patient preference …”
Section: Resultsmentioning
confidence: 75%
“…We excluded a further 233 studies and finally selected 38 studies, which included 145,066 thyroid nodules, for meta‐analysis (Fig. ) . Among the included studies, 4 were prospective and 34 were retrospective.…”
Section: Resultsmentioning
confidence: 99%